Limiting Acute Kidney Injury Progression In Sepsis: Study Protocol and Trial Simulation*. Issue 10 (October 2021) - Molinari, Luca; Heskia, Fabienne; Peerapornratana, Sadudee; Ronco, Claudio; Guzzi, Louis; Toback, Seth; Birch, Robert; Beyhaghi, Hadi; Kwan, Thomas; Kampf, J. Patrick; Yealy, Donald M.; Kellum, John A.
Abstract : OBJECTIVES: To describe study design considerations and to simulate a trial of biomarker-guided sepsis management aimed to reduce acute kidney injury (acute kidney injury). Tissue inhibitor of metalloproteinases-2 and insulin-like growth factor-binding protein 7, urinary biomarkers of cell-cycle arrest, and indicators of kidney stress can detect acute kidney injury before clinical manifestations. We sought to determine the event rates for acute kidney injury as a function of serial measurements of urinary (tissue inhibitor of metalloproteinases-2)(insulin-like growth factor-binding protein 7) in patients at risk of sepsis-associated acute kidney injury, so that an escalating series of kidney-sparing sepsis bundles based on international guidelines could be applied. DESIGN: We described the study protocol of "Limiting acute kidney injury Progression In Sepsis, " a phase 4, multicenter, adaptive, randomized controlled trial. We performed simulations to estimate the rates for the trial's primary endpoint using patient-level data from two previous studies (Sapphire and Protocolized Care for Early Septic Shock). SETTING: Academic and community ICUs. PATIENTS: Critically ill patients with sepsis or septic shock, without evidence of stage 2/3 acute kidney injury at enrollment. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Our primary endpoint is progression of two or more stages of acute kidney injury, death, or dialysis within 72 hours after enrollment. In the Sapphire simulation, 45 of 203 patients (22%) with sepsis met the endpoint. In Protocolized Care for Early Septic Shock, 144 of 607 patients (24%) with septic shock met the endpoint. In both simulations, (tissue inhibitor of metalloproteinases-2)(insulin-like growth factor-binding protein 7) patterns, suggested by Limiting acute kidney injury Progression In Sepsis protocol, stratified the risk for the endpoint from 6% (three negative tests) to 41% (for patients eligible for the highest level of kidney-sparing sepsis bundle) in Sapphire, and 14% (two negative tests) to 46% (for the highest level of kidney-sparing sepsis bundle) in Protocolized Care for Early Septic Shock. CONCLUSIONS: Findings of our Limiting acute kidney injury Progression In Sepsis trial simulation confirmed that (tissue inhibitor of metalloproteinases-2)(insulin-like growth factor-binding protein 7) could identify patients with different rates of progression to moderate/severe acute kidney injury, death, or dialysis in 72 hours. The Limiting acute kidney injury Progression In Sepsis protocol algorithm is therefore feasible in terms of identifying suitably high-risk individuals for kidney-sparing sepsis bundle. Abstract : Supplemental Digital Content is available in the text.